2016
DOI: 10.1155/2016/9849328
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Continuous Subcutaneous Insulin Infusion and Add-On Therapy with Sitagliptin in Patients with Newly Diagnosed Type 2 Diabetes Mellitus

Abstract: To identify a new regimen to optimize treatment for patients with newly diagnosed type 2 diabetes (T2DM) by short-term continuous subcutaneous insulin infusion (CSII) alone. Methods. 60 patients with newly diagnosed T2DM were randomized into two groups (n = 30 each) and treated for 2 weeks with CSII alone (CSII group) or with CSII plus sitagliptin (CSII + Sig group). The glycemic variability of the patients was measured using a continuous glucose monitoring system (CGMS) for the last 72 hours. A standard meal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Also, our data from the linear mixed-effects model showed a rapid BG drop during hemodialysis and a tendency for hypoglycemia in the subsequent nighttime period in maintenance hemodialysis patients with type 2 diabetes. Although DPP-4 inhibitors have been shown to improve BG variability in patients with type 2 diabetes in many randomized controlled trials (RCTs) [ 41 49 ] (see the table in the Electronic supplementary material), few studies have reported the same effect in maintenance hemodialysis patients [ 50 ]. Our study illustrates the usefulness of DPP-4 inhibitors in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, our data from the linear mixed-effects model showed a rapid BG drop during hemodialysis and a tendency for hypoglycemia in the subsequent nighttime period in maintenance hemodialysis patients with type 2 diabetes. Although DPP-4 inhibitors have been shown to improve BG variability in patients with type 2 diabetes in many randomized controlled trials (RCTs) [ 41 49 ] (see the table in the Electronic supplementary material), few studies have reported the same effect in maintenance hemodialysis patients [ 50 ]. Our study illustrates the usefulness of DPP-4 inhibitors in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of DPP-4 inhibitors to suppress BG variability in patients with type 2 diabetes has been shown in studies using CGM [ 51 , 52 ]. Furthermore, several RCTs using CGM found that BG variability is suppressed more effectively by DPP-4 inhibitors than by other agents such as sulfonylureas [ 41 , 42 ] and sodium glucose cotransporter 2 inhibitors [ 43 45 ] or by combination with insulin therapy [ 46 49 ]. The patients in these RCTs who showed suppressed BG variability with DPP-4 inhibitors had a mean age of less than 60 years [ 42 44 , 46 , 48 , 49 ], had HbA1c > 7% [ 41 44 , 46 49 ], were drug naïve [ 41 , 49 ], or had used metformin only [ 41 43 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the benefits obtained with the combination of CSII and glucose lowering agents in patients with T2D. Combination of sitagliptin with CSII for 2 weeks enabled attainment of similar glycemic targets versus CSII alone, but with lower glycemic variability and improved beta cell function . A study which randomized poorly controlled patients to CSII alone or CSII with the combination of exenatide for 3 days demonstrated increased glycemic variability with exenatide but reduced glucose AUC in an OGTT .…”
Section: What's the Evidence?mentioning
confidence: 99%
“…Overall, CGM is primarily recommended to patients with type 1 diabetes and those with type 2 diabetes on intensive insulin therapy or who experience dramatic glycemic variability. When appropriate, CGM can also be used in clinical research as a valuable tool for assessing and guiding treatment Real‐time CGM is mainly applicable to the following patients or conditions: children and adolescents with type 1 diabetes whose HbA 1c less than 7%.…”
Section: Clinical Indications For Cgm Technologymentioning
confidence: 99%